Amundsen Sea MAR simulations forced by ERAinterim - Marion, Donat-Magnin; Nicolas, Jourdain; Cécile, Agosta; Gallée Hubert; Charles, Amory; Christoph, Kittel; Xavier, Fettweis (Zenodo, 2019)
MAR simulations produced by Marion Donat-Magnin at IGE, Grenoble, France. This simulation is evaluated in the following article: Donat-Magnin, M., Jourdain, N. C., Gallée, H., Amory, C., Kittel, C., Fettweis, X., Wille, J. D., Favier, V., Drira, A., and Agosta, C. (2020). Interannual variability of summer surface mass balance and surface melting in the Amundsen sector, West Antarctica, The Cryosphere, 14, 229–249, https://doi.org/10.5194/tc-14-229-2020 Here are provided the monthly means over 1979-2017. Daily outputs available on demand. See netcdf metadata for more information. Note that the units for mlt (surface melt rate), rfz (refreezing rate), rnf (rainfall), rof (runoff or "net production of surface liquid water"), sbl (sublimation), smb (Surface Mass Balance) and snf (snowfall) are kg.m^{-2}.day^{-1} (i.e. mm water equivalent per day). Note that what is called runoff in the outputs is not actually a runoff (into the ocean) but more the net production of liquid water at the surface (which can either form ponds or flow into the ocean). The following variables are provided: CC Cloud Cover LHF Latent Heat Flux LWD Long Wave Downward LWU Long Wave Upward QQp Specific Humidity (pressure levels) QQz Specific Humidity (height levels) RH Relative Humidity SHF Sensible Heat Flux SIC Sea ice cover SP Surface Pressure ST Surface Temperature SWD Short Wave Downward SWU Short Wave Upward TI1 Ice/Snow Temperature (snow-layer levels) TTz Temperature (height levels) UUp x-Wind Speed component (pressure levels) UUz x-Wind Speed component (height levels) VVp y-Wind Speed component (pressure levels) VVz y-Wind Speed component (height levels) UVp Horizontal Wind Speed (pressure levels) UVz Horizontal Wind Speed (height levels) ZZp Geopotential Height (pressure levels) mlt Surface melt rate rfz Refreezing rate rnf Rainfall rof Runoff (i.e. net production of surface liquid water) sbl Sublimation smb Surface Mass Balance snf Snowfall : wrong time axis in v1.0 -> corrected in v1.1